Polyacrylamide hydrogel grafted onto polyethylene terephthalate textile via ultraviolet light-emitting diode photografting for oil/water separation - Naemuddin, Nurul Hazlina (2017)
This study was invented to provide a cheaper alternative filter material for oil/water separation application. Polyethylene terephthalate (PET) textiles with diameter of 4.5 cm were chemically grafted with a thin layer of polyacrylamide (PAAm) hydrogel via UV LED photopolymerisation system. From the grammages that were tested, 85 gsm PET was the most favourable to be used as a matrix. Based on the weight loss data the alkali treatment was optimised under the following condition i.e. 2 hours of treatment with 10 wt % of NaOH at 60 ºC. For the grafting process, the effects of UV curing time (5-30 minutes), positioning of filter paper as a spacer (M1 representing the filter paper at the bottom side only and M2 representing the filter papers at both top and bottom sides) as well as technique of grafting (immersion and dipping) were also taken into the account. The obtained samples were characterised using the basic characteristics such as the degree of grafting (DG) and Fourier transformed infrared spectroscopy (FTIR). The DG values for immersed samples were significantly higher (190 % for M1 and 160 % for M2) than dipped samples (90 % for M1 and 60 % for M2). The obtained samples were also characterised in terms of surface morphology by field emission scanning electron microscopy (FESEM), oil fouling, pure water permeability and oil/water permeability test. The results indicated that, the oil/water separation performance of the hydrogel-grafted filter materials (PAAm-g-HPET) were strongly influenced by the DG of grafted PAAm hydrogel. However, the immersion grafting technique was found not suitable to be used for commercialisation purposes because of the low water permeability due to hydrogel grafting inside pores as evidenced by FESEM images. The dipping grafting method with the positioning of M2 was selected to be the best method to deal with filtration in oil/water separation. Different UV curing time influenced the oil fouling behaviour of filter samples. Data concluded that 20 minutes of curing was the optimum time for hydrogel grafting. Wettability data indicated that the filter materials after undergoing alkali treatment as well as after being grafted with PAAm hydrogel changed from hydrophobic to hydrophilic. To some extent, this innovation has shown in the near future as promising device for oil/water separation.